Οι "Caesares" του Αυσονίου: Παρατηρήσεις και επισημάνσεις - ΠΑΠΠΑΣ, Βασίλειος Λ. (Byzantina Symmeikta, 2016)
Ausonius was a latin poet, born in Burdigala (Bordeaux), who, inter alios, composed the poetic work entitled "Caesares" between 379-383 A.D. This collection is an exposition of the lives of Roman emperors in verse (in hexameter and elegiac couplets). The collection is not complete. The work stops suddenly at the incomplete quatrain of Elagabalus. In this paper the author deals with the literary genre of the collection, the style of the poem, while he also attempts to trace the texts the poet used (Suetonius, Tacitus, the so[called Kaisergeschichte, Marius Maximus etc.). Finally he refers to the proposals concerning the missing part of the collection as put forth by various scholars in recent years.